Efficacy of technological intervention on production potential of diversified farming system in Panchmahals district, Gujarat - KHADDA, B S; LATA, KANAK; KUMAR, RAJ; JADAV, J K; RAI, A K; KHAJURIA, S (The Indian Journal of Agricultural Sciences, 2014)
The present study the efficacy of technological intervention on production potential of diversified farming system was conducted at Godhra, Kalol, Halol and Lunawara Talukas of Panchmahals district of Central Gujarat during the year 2010-12. Seven components like maize, fodder, vegetables, fruit crops, dairy, goatry and poultry were considered for study. Keeping these aspects in view, the influence of technological intervention on scientific farming system with comparisons to traditional farming system was worked out. The average land holding of selected farmers was 1.22 ha. Results of the study revealed that the production of maize, fodder, vegetables, fruit crops, dairy, goatry and poultry under scientific farming system was significantly influenced as compared to traditional farming system. The percentage increase in the production of maize, hybrid Napier and lucerne, tomatoes, chilly, brinjal, fruits, milk and egg in scientific farming system was recorded 47.2, 45.52, 37.32, 41.46, 41.66, 65.99, 37.25 and 152.29 respectively over traditional system. Similarly the average net return and cost benefit ratio was also computed significantly higher in scientific than traditional farming system. Overall observations after integrating different components of farming system, it may inferred that the production, productivity, economic returns, balance nutrition along with better employment can be improved by adopting diversified farming system under semi-arid ecosystem of western India which have not only alleviated the socio-economic condition of farmers, but also provided sustainability in productivity by following of various scientific technologies over traditional farming.